Seasonal influenza vaccination and absenteeism in health-care workers in two subsequent influenza seasons (2016/17 and 2017/18) in an Italian pediatric hospital - Salvatore Zaffina; Francesco Gilardi; Caterina Rizzo; Serena Sannino; Rita Brugaletta; Annapaola Santoro; Guido Castelli Gattinara; Marta Luisa Ciofi degli Atti; Massimiliano Raponi; Maria Rosaria Vinci (Taylor & Francis Group, 2019)
Background: Seasonal influenza in Health-Care Workers (HCWs) is a topic of growing interest in public health for its organizational implications. The study aims at measuring absenteeism due to influenza in HCWs of an Italian pediatric hospital. Research design and methods: A retrospective observational study on absenteeism for influenza and influenza-like illness was carried out on all hospital HCWs. Sickness absences up to 5 days and vaccination status of HCWs were recorded during the last two years (2016/2017, /2018). Average sickness absenteeism rate in vaccinated and unvaccinated HCWs and total working days lost were estimated. Daily mean cost for HCW was calculated in order to define the non-vaccination costs. Results: In this study, the authors analyzed the overlapping between the trend of weekly sickness absenteeism and the morbidity rate associated with influenza epidemics in adults living in the Lazio region, Italy. An excess of 0.38 (p = 0.03) and 0.46 (p = 0.01) of average days lost was recorded in unvaccinated HCWs in the 2016/2017 and 2017/2018 epidemic seasons. The total amount of days lost in unvaccinated HCWs is 1.485,4 with a total cost of € 252.060,54. Conclusions: Seasonal influenza vaccination confirms its key role in preventing outbreaks of influenza and promoting HCWs health.